Self-Doping and the Mott-Kondo Scenario for Infinite-Layer Nickelate Superconductors - Yang, Yi-feng; Zhang, Guang-Ming (Frontiers in Physics, 2022)
We give a brief review of the Mott-Kondo scenario and its consequence in the recently-discovered infinite-layer nickelate superconductors. We argue that the parent state is a self-doped Mott insulator and propose an effective t-J-K model to account for its low-energy properties. At small doping, the model describes a low carrier density Kondo system with incoherent Kondo scattering at finite temperatures, in good agreement with experimental observation of the logarithmic temperature dependence of electric resistivity. Upon increasing Sr doping, the model predicts a breakdown of the Kondo effect, which provides a potential explanation of the non-Fermi liquid behavior of the electric resistivity with a power law scaling over a wide range of the temperature. Unconventional superconductivity is shown to undergo a transition from nodeless (d+is)-wave to nodal d-wave near the critical doping due to competition of the Kondo and Heisenberg superexchange interactions. The presence of different pairing symmetry may be supported by recent tunneling measurements.